2016
DOI: 10.1073/pnas.1600544113
|View full text |Cite
|
Sign up to set email alerts
|

Yellow fever virus capsid protein is a potent suppressor of RNA silencing that binds double-stranded RNA

Abstract: Mosquito-borne flaviviruses, including yellow fever virus (YFV), Zika virus (ZIKV), and West Nile virus (WNV), profoundly affect human health. The successful transmission of these viruses to a human host depends on the pathogen's ability to overcome a potentially sterilizing immune response in the vector mosquito. Similar to other invertebrate animals and plants, the mosquito's RNA silencing pathway comprises its primary antiviral defense. Although a diverse range of plant and insect viruses has been found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 58 publications
6
108
0
3
Order By: Relevance
“…Expression of influenza virus NS1, vaccinia virus E3L, reovirus σ3 and Nodamura virus (NoV) B2 proteins inhibits RNAi in plants and/or insect cells (Lichner et al, ; Bucher et al, ; Delgadillo et al, ; Li et al, ). In mammalian cells, a plethora of mammalian virus‐encoded VSRs, including primate foamy virus type 1 (PFV‐1) Tas, NoV B2, HCV core, IAV NS1, HIV Tat, Ebola VP35, VP30 and VP40, CoV N, SARS‐CoV 7a, YFV capsid, DENV NS4B, human enterovirus 71 (HEV 71) 3A and adenovirus virus‐associated RNA I (VA1), can reduce shRNA/siRNA‐mediated knockdown of reporter genes (Table ) (Lu & Cullen, ; Andersson et al, ; Lecellier et al, ; Sullivan & Ganem, ; Wang et al, ; Haasnoot et al, ; Chen et al, ; de Vries et al, ; Karjee et al, ; Fabozzi et al, ; Kakumani et al, ; Cui et al, ; Samuel et al, ; Qiu et al, ). Most viral proteins identified thus far that display VSR activity share the ability to bind dsRNA and mutations that affect their dsRNA‐binding domain block VSR activity, arguing that their principal mode of action is sequestration of dsRNA from Dicer (Table ).…”
Section: Viral Determinants Of Antiviral Rnaimentioning
confidence: 99%
“…Expression of influenza virus NS1, vaccinia virus E3L, reovirus σ3 and Nodamura virus (NoV) B2 proteins inhibits RNAi in plants and/or insect cells (Lichner et al, ; Bucher et al, ; Delgadillo et al, ; Li et al, ). In mammalian cells, a plethora of mammalian virus‐encoded VSRs, including primate foamy virus type 1 (PFV‐1) Tas, NoV B2, HCV core, IAV NS1, HIV Tat, Ebola VP35, VP30 and VP40, CoV N, SARS‐CoV 7a, YFV capsid, DENV NS4B, human enterovirus 71 (HEV 71) 3A and adenovirus virus‐associated RNA I (VA1), can reduce shRNA/siRNA‐mediated knockdown of reporter genes (Table ) (Lu & Cullen, ; Andersson et al, ; Lecellier et al, ; Sullivan & Ganem, ; Wang et al, ; Haasnoot et al, ; Chen et al, ; de Vries et al, ; Karjee et al, ; Fabozzi et al, ; Kakumani et al, ; Cui et al, ; Samuel et al, ; Qiu et al, ). Most viral proteins identified thus far that display VSR activity share the ability to bind dsRNA and mutations that affect their dsRNA‐binding domain block VSR activity, arguing that their principal mode of action is sequestration of dsRNA from Dicer (Table ).…”
Section: Viral Determinants Of Antiviral Rnaimentioning
confidence: 99%
“…The C protein can migrate to the nucleus of flavivirus-infected cells [97] and modulate functions of host nuclear proteins [94], e.g., acting as a histone mimic, interacting with core histones, and disrupting nucleosome formation [98], or interacting with other host nuclear proteins, such as heterogeneous nuclear ribonucleoprotein K (hnRNP-K) [99], death domain-associated protein 6 (DAXX) [100], and nucleolin (NCL) [101]. Finally, the C protein can be involved in the inhibition of the RNA silencing via interference with the host ribonuclease Dicer [102].…”
Section: Intrinsic Disorder and Functionality Of Mature Alkv Proteinsmentioning
confidence: 99%
“…Interestingly, Myles and colleagues recently showed that the YFV C protein counteracts the RNA interference pathway in Ae. aegypti by protecting double-stranded viral RNA from Dicer-2-induced cleavage [50]. No amino acid sequence responsible for this effect has been identified.…”
Section: Resultsmentioning
confidence: 99%
“…This unique mutation and/or these differences in C protein diversity could modulate their RNA interference suppression activities. It is unfortunate that Myles and colleagues [50] did not provide information on the viral strain they used.…”
Section: Resultsmentioning
confidence: 99%